Development and evaluation of culturally sensitive psychosocial interventions for under-served people in primary care - Lovell, Karina (BioMed Central, 2014)
BACKGROUND: Psychological therapy is effective for symptoms of mental distress, but many groups with high levels of mental distress face significant barriers in terms of access to care, as current interventions may not be sensitive to their needs or their understanding of mental health. There is a need to develop forms of psychological therapy that are acceptable to these groups, feasible to deliver in routine settings, and clinically and cost effective. METHODS: We developed a culturally sensitive wellbeing intervention with individual, group and sign-posting elements, and tested its feasibility and acceptability for patients from ethnic minorities and older people in an exploratory randomised trial. RESULTS: We recruited 57 patients (57% of our target) from 4 disadvantaged localities in the NW of England. The results of the exploratory trial suggest that the group receiving the wellbeing interventions improved compared to the group receiving usual care. For elders, the largest effects were on CORE-OM and PHQ-9. For ethnic minority patients, the largest effect was on PHQ-9. Qualitative data suggested that patients found the intervention acceptable, both in terms of content and delivery. CONCLUSIONS: This exploratory trial provides some evidence of the efficacy and acceptability of a wellbeing intervention for older and ethnic minority groups experiencing anxiety and depression, although challenges in recruitment and engagement remain. Evidence from our exploratory study of wellbeing interventions should inform new substantive trial designs. TRIAL REGISTRATION: Current controlled trials ISRCTN68572159